Kiev's EU ambitions - Eberhard Schneider; Christoph Saurenbach (Stiftung Wissenschaft und Politik (SWP), 2005)
The adoption of the EU-Ukraine Action Plan and the changed rhetoric of the new leadership in Kiev suggest a paradigm shift in Ukrainian foreign policy. The new government - unlike its predecessor, which failed to back up its EU-friendly rhetoric with specific actions in the same vein - has announced radical internal reforms and the adaptation of Ukrainian legislation to EU standards. The country's new President, Victor Yushchenko, has made it absolutely clear that he sees a place for his country in the European Union. In 2006 Ukraine intends to submit an official application for EU membership and hopes that negotiations on its accession will begin in 2007. (SWP-Comments / SWP)
Keywords: 320